2019
DOI: 10.1038/s41598-018-37458-x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of HIV-1 suggests that Ugandan fishing communities are a sink for, not a source of, virus from general populations

Abstract: Although fishing communities (FCs) in Uganda are disproportionately affected by HIV-1 relative to the general population (GP), the transmission dynamics are not completely understood. We earlier found most HIV-1 transmissions to occur within FCs of Lake Victoria. Here, we test the hypothesis that HIV-1 transmission in FCs is isolated from networks in the GP. We used phylogeography to reconstruct the geospatial viral migration patterns in 8 FCs and 2 GP cohorts and a Bayesian phylogenetic inference in BEAST v1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
54
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 58 publications
(84 reference statements)
4
54
2
Order By: Relevance
“…Among R15 survey participants, 25% of women out-migrated compared to 22% of men (Poisson regression p-value < 0.001), and of R16 participants, 24% of women were in-migrants compared to 19% of men (Poisson regression p-value < 0.001). In-and out-migrants were less likely to be married and to work in agriculture compared to residents ( 4172 (53) 636 (45) 708 (49) Never married 1969 (24) 509 (27) 404 (18) 2933 (37) 614 (43) 570 (39) Previously married 1593 (19) 363 (19) 0.003 462 (21) <0.001 800 (10) 172 (12) <0.001…”
Section: Cross-community Migration Is Pervasive In Rural Ugandamentioning
confidence: 99%
See 1 more Smart Citation
“…Among R15 survey participants, 25% of women out-migrated compared to 22% of men (Poisson regression p-value < 0.001), and of R16 participants, 24% of women were in-migrants compared to 19% of men (Poisson regression p-value < 0.001). In-and out-migrants were less likely to be married and to work in agriculture compared to residents ( 4172 (53) 636 (45) 708 (49) Never married 1969 (24) 509 (27) 404 (18) 2933 (37) 614 (43) 570 (39) Previously married 1593 (19) 363 (19) 0.003 462 (21) <0.001 800 (10) 172 (12) <0.001…”
Section: Cross-community Migration Is Pervasive In Rural Ugandamentioning
confidence: 99%
“…Educational status (%) None 1392 (17) 352 (19) 454 (20) 1684 (21) 312 (22) 371 (26) Primary 3514 (42) 757 (41) 882 (40) 3589 (45) 609 (43) 601 (41) Secondary or higher (45) 741 (40) 918 (41) 1631 21228 (16) 251 (17) Bar/Restaurant work 1133 14238 17312 22Student 1434 (17) 254 (14) 138 (6) 1923 25267 (19) 109 (8) Trader/Shop keeper 1207 (15) 294 (16) 416 (19) 1098 14201 14199 14Other 1443 (17) 400 ( 1030 (55) 1124 (51) 5132 65753 53611 (42) Trading community 1158 (14) 337 (18) 465 (21) 842 11225 (16) 251 (17) Fish landing site 1549 (19) 495 ( 571 (26) 614 (43) 821…”
Section: Cross-community Migration Is Pervasive In Rural Ugandamentioning
confidence: 99%
“…They can be used for identifying and monitoring of HIV transmission clusters, identification of local HIV outbreaks and for targeting subsequent public health interventions [2][3][4]. When the location from which the HIV genomes were obtained is known, phylogeographic methods can be used to describe HIV migration within various geographic regions [4][5][6], or among different epidemiological risk groups.…”
Section: Introductionmentioning
confidence: 99%
“…Such groups have high incidence for HIV. These groups include sexual workers, fish folk community and truck drivers [6] [7] [8] [9]. It was observed that sex workers, their clients and regular partners of clients, contributed between 7% and 11% of new infections in Uganda, Swaziland and Zambia [8].…”
Section: Introductionmentioning
confidence: 99%